THE FULFILMENT OF MASLOW’S HIERARCHY OF NEEDS ON MAIN CHARACTERS IN “ENCANTO” MOVIE: A HUMANISTIC STUDY - Anisha Bunga Armethia Fitriane; Abdilah Nugroho (Jurusan Sastra Indonesia, 2022)
The purpose of this study is to find out how the efforts made by the main characters in Encanto Movie (2021) meet their needs and analyse it according to Maslow's theory. This research method is defined as a qualitative method. The author limits the data by classifying into five groups of different levels of needs based on Maslow's hierarchy of needs theory. In this study, it can be concluded that the main character has levels of needs ranging from the most basic to the most important needs. For example, on Maribel, the author found that of Maslow's 5 levels of needs, there are 5 needs so that it can be said that all of her needs have been met and the most important are the needs for love and belonging, and self-actualization. As for Abuela, the author finds that out of these 5 levels of needs, there is only 1 level of need that must be met by her, namely the needs for self-actualization.Keyword: Hierarchy of needs, Family Relation, Humanistic psychology